Empathetic leadership and employees’ innovative behavior: examining the roles of career adaptability and uncertainty avoidance - Ma, Guangya; Wu, Weilin; Liu, Chenlin; Ji, Junhan; Gao, Xiaoxiao (Frontiers in Psychology, 2024)
Introduction: Career construction theory proposes that adaptivity affects career adapting through career adaptability. However, research on the mechanism of this pathway remains scarce. By applying career construction theory and conservation of resources theory, we hypothesize that career adaptability (concern, control, curiosity, and confidence) mediates the relationship between empathetic leadership (adaptivity) and innovative behaviour (career adapting). Moreover, we posit that uncertain avoidance moderates the mediating mechanism. Methods: Our study used SPSS23 and bootstrap methods (PROCESS) to test the proposed model. The sample comprised 301 employees from different firms in various industries. In this study, empathetic leadership-5, career adaptability-24, uncertainty avoidance-5, and innovative behaviour-6 scales were used to measure empathetic leadership, career adaptability, and uncertainty avoidance. Results: The results revealed that (1) empathetic leadership is positively related to employees’ innovative behaviour. (2) Concern (H2a), control (H2b), curiosity (H2c), and confidence (H2d) mediate the relations between empathetic leadership and employee’s innovative behaviour. (3) Uncertainty avoidance moderates the relationship between empathetic leadership and concern (H3a), control (H3b), curiosity (H3c), and confidence (H3d), such that this relationship is stronger when uncertainty avoidance is higher. (4) Uncertainty avoidance moderates the indirect relationship between empathetic leadership and employee innovative behaviour through concern (H4a), control (H4b), curiosity (H4c), and confidence (H4d), such that this indirect relationship will be stronger when uncertainty avoidance is high than when it is low. Conclusion: We investigated how empathetic leadership affects innovative behaviour. Based on career construction theory and conservation of resources theory, we also tested the hypothesis that concern, control, curiosity, and confidence play mediating roles in linking empathetic leadership (career adaptivity) to innovative behaviour (career adapting). In addition, this study found that uncertainty avoidance does not always have negative effects. People with a high uncertainty avoidance tendency may be dependent more on empathetic leadership to improve their career adaptability, which promotes their innovative behaviour.